2007
DOI: 10.1016/j.jvs.2006.09.057
|View full text |Cite
|
Sign up to set email alerts
|

Free-floating thrombus of the carotid artery: Literature review and case reports

Abstract: FFT is more frequently reported in men than women, with a ratio of nearly 2:1 (P < .0001), and at a younger age than in most patients with carotid disease (P < .0001 when compared with North American Symptomatic Carotid Endarterectomy Trial, European Carotid Surgery Trial, and Asymptomatic Carotid Surgery Trial). Symptoms are present in 92% of patients. There was a trend for patients with FFT to be hypercoagulable (47% of those serologically tested). The internal carotid artery was the most commonly affected (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
219
1
11

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(241 citation statements)
references
References 47 publications
10
219
1
11
Order By: Relevance
“…The main risk attached to these lesions is the possibility of cerebral embolism caused by detachment of clot fragments. In 75% of all cases, the thrombus develops in the internal carotid [4]. In the other 25%, the common carotid is involved, as it was in our patient.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…The main risk attached to these lesions is the possibility of cerebral embolism caused by detachment of clot fragments. In 75% of all cases, the thrombus develops in the internal carotid [4]. In the other 25%, the common carotid is involved, as it was in our patient.…”
Section: Discussionsupporting
confidence: 64%
“…In the vast majority of cases (92%) [4], the diagnosis is made after the patient develops clinical signs of cerebral ischemia. The main risk attached to these lesions is the possibility of cerebral embolism caused by detachment of clot fragments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ultimately demonstrated both medical and surgical management as being used in the treatment of MAPs, with neither being deemed as superior [1]. Meanwhile, for symptomatic lesions specifically described as mobile plaques, Ko et al, reported two cases with symptomatic MAP that were treated with ticlodipine 200mg daily [6,7].…”
Section: Resultsmentioning
confidence: 99%
“…A mobile atheromatous floating carotid plaque is an infrequent pathology, which occurs due to unknown mechanisms, and is often responsible for drastic outcomes [1]. Diagnostic imaging demonstrating mobile atheromatous plaque (MAP) at the carotid bifurcation or at the origin of the internal carotid artery (ICA) is a rare finding [2].…”
Section: Introductionmentioning
confidence: 99%